Philosophy of Statistics. - Prasanta S. Bandyopadhyay (North Holland, 2011)
Statisticians and philosophers of science have many common interests but restricted communication with each other. This volume aims to remedy this by providing research in the area of philosophy of statistics by encouraging experts to communicate with one another without feeling 'restricted' by their disciplines.
Data, Data, Everywhere: Statistical Issues in Data Mining / Choh Man Teng -- pt. XIII An Application of Statistics to Climate Change -- An Application of Statistics in Climate Change: Detection of Nonlinear Changes in a Streamflow Timing Measure in the Columbia and Missouri Headwaters / Johnnie Moore -- pt. XIV Historical Approaches to Probability/Statistics -- The Subjective and the Objective / Sandy L. Zabell -- Probability in Ancient India / C.K. Raju.
Keywords: Statistics -- Philosophy; Probabilities; MATHEMATICS -- Applied; MATHEMATICS -- Probability & Statistics -- General; Probabilities